The Contribution of Public Relations in Organizational Success A Case of Electricity Company of Ghana - Best-Gavi, Juliana (UniMAC - GIJ, 2020)
The goal of this study is to examine the contribution of Public Relations in organizational success at the Electricity Company of Ghana. The focus of the study was on the recent implementation of Public Relations practices and how they improve organizational effectiveness in government organizations. The researcher employed some objectives in order to: establish the effect of public relations communicator roles on organizational effectiveness at ECG; determine the effect of public relations practice models on enhancing organizational effectiveness at ECG and establish the effect of public relations hierarchical placement on organizational effectiveness at ECG. The study was based on the Excellence and Systems theories of Public Relations and models of organizational effectiveness. The study employed the qualitative approach and data was collected through interviews. Data analysis was done, the findings revealed that Public Relations had a great positive effect on organizational effectiveness. In addition, the nature of PR practice at ECG met the requirement of the Excellence Theory and effectively played the role required by the Systems Theory. Furthermore, the two- way symmetrical model was amply applied and PR was part of Management. The researcher recommends that the practice of excellent PR should be encouraged in the Business industry in Ghana.
THESIS